2012
DOI: 10.3732/ajb.1100546
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal and environmental changes of mycorrhizal associations and heterotrophy levels in mixotrophicPyrola japonica(Ericaceae) growing under different light environments

Abstract: The mixotrophic P. japonica undergoes changes in mycorrhizal symbionts and carbon nutrition according to light availability. Our results suggest that during Pyroleae evolution, a tendency to increased heterotrophy emerged in the Pyrola/Orthilia clade.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
58
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(66 citation statements)
references
References 54 publications
(143 reference statements)
6
58
1
Order By: Relevance
“…subaphylla are mainly characterized by green scapes with well developed leaves (hereafter, the GL morphotype) and reddish scapes with rudimentary scale-like leaves (the RS morphotype), respectively, a third morphotype that has reddish or green scapes with intermediate leaf sizes and does not correspond to the two varieties is also found (the RL morphotype) (Shutoh et al, 2016). Consistent with a previous report that leaf size can be a rough predictor of the degree of mycoheterotrophy (Hynson et al, 2009), the GL and RS morphotypes exhibit different degrees of mycoheterotrophy: the GL morphotype exhibits partial mycoheterotrophy and the RS morphotype exhibits nearly full or full mycoheterotrophy (Takahashi, 1993;Matsuda et al, 2012;Shutoh et al, 2016). Because they have distinct chloroplast haplotypes, these three morphotypes can be genetically differentiated (Shutoh et al, 2016).…”
Section: Introductionsupporting
confidence: 83%
“…subaphylla are mainly characterized by green scapes with well developed leaves (hereafter, the GL morphotype) and reddish scapes with rudimentary scale-like leaves (the RS morphotype), respectively, a third morphotype that has reddish or green scapes with intermediate leaf sizes and does not correspond to the two varieties is also found (the RL morphotype) (Shutoh et al, 2016). Consistent with a previous report that leaf size can be a rough predictor of the degree of mycoheterotrophy (Hynson et al, 2009), the GL and RS morphotypes exhibit different degrees of mycoheterotrophy: the GL morphotype exhibits partial mycoheterotrophy and the RS morphotype exhibits nearly full or full mycoheterotrophy (Takahashi, 1993;Matsuda et al, 2012;Shutoh et al, 2016). Because they have distinct chloroplast haplotypes, these three morphotypes can be genetically differentiated (Shutoh et al, 2016).…”
Section: Introductionsupporting
confidence: 83%
“…The greater 13 C enrichment found on average in FMH Orchidaceae relative to Ericaceae may be due to differences in the biochemical make-up of tissues (sensu Gebauer and Schulze, 1991;Badeck et al, 2005;Cernusak et al, 2009) or, again, possibly due to greater relative fungal C contributions from the digestion of pelotons entailing little 13 C discrimination, as opposed to active C transport which discriminates against 13 C. For PMH plants, the situation is more complex, because they are composed of C from two different origins, atmospheric CO 2 gained through C 3 photosynthesis and organic matter from the fungal source, and the ratios of these two sources can vary based on environmental factors. For example, light availability has been shown to be an important determinant for the 13 C enrichment of some PMH orchids and at least one PMH ericaceous species Matsuda et al, 2012). These studies found that as light becomes more limiting, some partial mycoheterotrophs increase their dependency on 13 C-enriched fungal C. So, if some of the PMH species included in this study were collected in different light environments, this could have led to significant differences in their e 13 C values.…”
Section: Drivers Of Nitrogen Concentrations Among Plant Families and mentioning
confidence: 93%
“…Finally, much of the intra-and interspecific variation in N concentrations, and 13 C and 15 N enrichment of partial mycoheterotrophs is probably due to the environment in which these plants are subsisting Hynson et al, 2012;Matsuda et al, 2012). So, measurements of stable isotope composition throughout the life cycle of individual plants and over time within adult plants could add valuable explanatory power to these models, as would data on light environment, leaf chlorophyll concentrations, and plant-water and plant-nutrient relations Stöckel et al, 2011;Hynson et al, 2012;Matsuda et al, 2012).…”
Section: Future Directionsmentioning
confidence: 99%
“…Though well documented, this remarkable developmental metamorphosis in changing mycobionts is not understood but concisely commented on by Hynson et al (2012). In contrast, Matsuda et al (2012) found various basidiomycetous symbionts of the genera Russula, Amanita, Clavulina, Inocybe, Tomentella and Tricholoma, but no Sebacina in P. japonica in a deciduous broadleaf forest with dominating Quercus serrata and Q. acutissima, in the Mie Prefecture, central Japan. The finding of Group B sebacinalean fungi as EEMs on adult roots of Pyroleae is somewhat unexpected, since EEM fungi normally belong to taxa that are also able to form ECM associations.…”
Section: Ectendomycorrhizae (Eem)mentioning
confidence: 99%